Screening of SNPs Associated with Egg Production in Two Strains of White Leghorn - Kachchhi, Ankit V; Patel, Ashish C; Parmar, Glory S; Patel, Devanshi V; Koringa, Prakash G; Savaliya, F P (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
The poultry industry in India has become a prominent and rapidly expanding sector of the agro-animal industry, and is recognized as an important source of animal protein in the country. Through genetic analysis, Single Nucleotide Polymorphisms (SNPs) can help identify variations in DNA sequences that are linked to traits such as egg quality, quantity, fertility, hatchability, and other important aspects of egg production in poultry or other egg-laying species. The aim of the present study was to screen the SNPs in the candidate genes associated with egg production, viz., MC4R, MTNR1A, DRD1, PRLR and VLDLR and their association with egg production at the age of 64 weeks in two strains of White Leghorn, viz., Anand Bantamized White Leghorn (ABWLH) and Anand Synthetic White Leghorn (ASWLH). The amplicon-sequenced data of a total of 96 birds for these genes were collected in ‘fastq’ format and various SNPs were identified. A total of 143 detected SNPs were filtered based on read depth and QUAL score and 60 SNPs were discarded after filtering variants. Out of the remaining 83 SNPs, 69 SNPs were previously reported, while 14 were found as novel. Association analysis showed that one of the SNPs found in the MC4R gene was significantly associated with the egg production in both ABWLH and ASWLH population.